The principle of prohibition and the closing of international law as a regulatory system; Hans Kelsen and the history of a boat - Luterstein, Natalia M. (Revista Tribuna Internacional, 2017)
This papers examines the impact of the dictum of the Permanent Court of International Justice in the “S.S. Lotus” case when it stated that “restrictions upon the independence of States cannot be presumed” and that “the rules of law binding upon States therefore emanate from their own free will as expressed in conventions or by usages generally accepted as expressing principles of law” on the interpretation and the functioning of the international legal order in light of the theory of Hans Kelsen and the critics advanced by Carlos Alchourrón and Eugenio Bulygin regarding the principle of prohibition and completeness of the normative legal systems.